2017
DOI: 10.3390/w9120976
|View full text |Cite
|
Sign up to set email alerts
|

Water Experts’ Perception of Risk for New and Unfamiliar Water Projects

Abstract: Abstract:In the context of a changing urban environment and increasing demand due to population growth, alternative water sources must be explored in order to create future water security. Risk assessments play a pivotal role in the take-up of new and unfamiliar water projects, acting as a decision-making tool for business cases. Perceptions of risk ultimately drive risk assessment processes, therefore providing insight into understanding projects that proceed and those that do not. Yet there is limited inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Saurí and Arahuetes (2019) have suggested that public trust should extend beyond trust in the authorities to include the many stakeholders intervening in the process, such as academics and politicians; processes intended at building public trust should be a lot broader than has conventionally been practiced. Kosovac et al (2017) recommended the implementation of trust-building activities between water practitioners and the public.…”
Section: Disgust As More Than Simple Revulsionmentioning
confidence: 99%
“…Saurí and Arahuetes (2019) have suggested that public trust should extend beyond trust in the authorities to include the many stakeholders intervening in the process, such as academics and politicians; processes intended at building public trust should be a lot broader than has conventionally been practiced. Kosovac et al (2017) recommended the implementation of trust-building activities between water practitioners and the public.…”
Section: Disgust As More Than Simple Revulsionmentioning
confidence: 99%
“…However, in the following twenty years, with the rapid development of science and technology, the application scope of recycled water has expanded. In recent years, because of the emergence of wastewater treatment technologies like membrane technology [11], the recycled water obtained with deep treatment could meet the standards [12,13] of drinking water. Wastewater treatment technology is not the major difficulty that restricts the popularization of recycled water use.…”
Section: Introductionmentioning
confidence: 99%
“…However, 63% of the residents were against the project so that it was abolished. The public's acceptance degree to reclaimed water reuse is crucial to the successful implementation of the project [3,4]. Therefore, scholars have carried out a considerable number of studies to test the factors that affect the public's willingness to accept reclaimed water.…”
Section: Introductionmentioning
confidence: 99%